Implementing the tracking of 1500 m runners using Open CV - Yang, Y.; Lee, X.; Enomoto, Y. (Journal of Physical Education and Sport, 2023)
Purpose: This study uses OpenCV to recognise and track runners in a 1500 m race video, output their actual coordinates and calculate their actual running distance and speed. By tracking middle-distance runners, their running performance can be analysed. The traditional method of video recording and analysis for a 1500 m race can be replaced by artificial intelligence techniques.